Case Report: A Case of Myeloproliferative Neoplasm Complicated by Alopecia Areata - Tamai, Yotaro; Teshima, Shinichi; Tsunoda, Shun; Kamata, Wataru; Sato, Shuku (Frontiers in Medicine, 2022)
Myeloproliferative neoplasms (MPNs) are caused by genetic abnormalities in the stem cells and manifest with various systemic symptoms. Here, we describe a case of MPN complicated by alopecia areata. A 51-year-old woman visited our hematology department for further evaluation of a slight platelet elevation. Her recent medical history included 3 years of concurrent severe alopecia, mild fatigue, and hot flashes but no fever and weight loss. Physical examination revealed unilateral hair loss on the entire body but no hepatosplenomegaly. Laboratory analysis revealed a normal hemoglobin level, normal white blood cell count, and platelet count of 377,000/L. Genetic testing confirmed the presence of the JAK2 V617F mutation. Bone marrow examination revealed no morphologic dysplasia in any stem cell lineage and no fibrotic change. Skin biopsy revealed lymphocyte infiltration around the hair follicles. We diagnosed MPN, unclassifiable, which was believed to be the cause of alopecia. About 6 months after treatment with ruxolitinib began, the patient’s hair growth dramatically improved. The differential diagnosis of MPNs should include hematological diseases when affected patients have alopecia areata.